Angiokeratoma of Fordyce response to long pulsed Nd:YAG laser treatment. Issue 1 (3rd November 2015) - Zeng, Ying; Zhan, Kui; Xie, Wen‐Lian; Lin, Qiong‐Zhu
ABSTRACT: Angiokeratoma of Fordyce can be easily diagnosed by their typical erythra and cured by varied therapeutic methods including surgery, electrocoagulation, cryotherapy, or various laser systems. Which are the optimal therapeutic methods? There are no consentaneous opinions in the reported articles. We present our characteristic treatment with the application of long pulsed neodymium–dopedyttrium–aluminum–garne (lpNd:YAG) laser in the treatment of angiokeratoma of Fordyce. A 1064 nm lpNd:YAG laser (spot size: 5 mm/7 mm, energy:90–130 J/cm 2, and pulse duration: 10–20 ms.) was used to treat the patient's lesions. The desirable clinical endpoint of the treatment was lesions shrunk and turned pallor immediately after the irradiation. The treatment interval was at least 8 weeks. Of the 11 patients, 9 of them were cured and 2 of them were improved. The mean treatment sessions were 2.2 times. None of them had a scar formation and any other side effects. All of them were satisfied with the treatment results. We conclude that angiokeratoma of Fordyce responded well to lpNd:YAG laser treatment. It provided a simple, rapid, and no bleeding treatment in treating Angiokeratoma of Fordyce.